1992
DOI: 10.1002/jat.2550120105
|View full text |Cite
|
Sign up to set email alerts
|

Hexachlorobenzene (HCB) suppresses circulating progesterone concentrations during the luteal phase in the cynomolgus monkey

Abstract: Hexachlorobenzene (HCB) is a known reproductive toxin. However, the full spectrum of its reproductive toxicity is unknown. Consequently, the effect of HCB on serum oestradiol (E2) and progesterone (P4) concentrations during the follicular (days 1-9), periovulatory (days 10-14) and luteal (days 15 to beginning of next menses) phases was investigated in the spontaneously cycling cynomolgus monkey. Adult female cynomolgus monkeys (n = 16) were randomly assigned to one of four treatment groups and orally doses wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
1

Year Published

1992
1992
2012
2012

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 20 publications
1
19
1
Order By: Relevance
“…For example, hexachlorobenzene (HCB) has been shown to suppress luteal progesterone synthesis in cynomolgus monkeys (43). We and other investigators (9) have not found that HCB binds to ER (Table 1), which would categorize it as a potential endocrine disruptor but not xenoestrogen.…”
Section: Discussionmentioning
confidence: 82%
“…For example, hexachlorobenzene (HCB) has been shown to suppress luteal progesterone synthesis in cynomolgus monkeys (43). We and other investigators (9) have not found that HCB binds to ER (Table 1), which would categorize it as a potential endocrine disruptor but not xenoestrogen.…”
Section: Discussionmentioning
confidence: 82%
“…However, a nonhuman primate study demonstrated that HCB exposure induced a dose-dependent suppression of luteal serum progesterone (Foster et al 1992). Suppressed luteal progesterone may increase the likelihood of implantation failure due to reduced endometrial maturation or of early pregnancy loss from inadequately low levels of progesterone production (Jones and Wentz 1976).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported to induce hepatic and thyroid neoplasm,2 3 porphyria,4 5 and hormonal disruption, including alterations in progesterone and testosterone concentrations,6 7 depletion of triiodothyronine (T3) and thyroxine (T4),8goitre,9 and hypothyroidism 10. Very little information on effects on liver function is available, although effects on hepatic Îł-glutamyl transpeptidase have been described in rats 11…”
mentioning
confidence: 99%